A laboratory study to assess the formation of effluent volatile compounds and disinfection by‐products during chemomechanical preparation of infected root canals and application of activated carbon for their removal. (18th December 2020) - Ioannidis, K.; Batty, C.; Turner, C.; Smith, D.; Mannocci, F.; Deb, S.
Abstract: Aim: To assess in a laboratory setting using extracted teeth the formation of volatile compounds (VOCs) and disinfection by‐products (DBPs) in effluent aliquots, during chemomechanical preparation of artificially infected root canal specimens, and determine the role of silver‐impregnated activated carbon (Ag‐AC) in their removal. Methodology: Single‐rooted human teeth were decoronated to obtain 15 mm‐long root specimens and a nutrient‐stressed multispecies biofilm was grown in the root canals. Specimens were randomly assigned into three groups [Group 1; instrumentation with rotary files and irrigation with sterile saline, Groups 2 and 3; instrumentation with rotary files and irrigation with 2.5% NaOCl and 17% EDTA]. A portable medical suction device was used to collect the effluent aliquots during root canal irrigation. In Groups 1 and 2, the reaction products of the collected effluents were analysed by selected ion flow tube mass spectrometry (SIFT‐MS). The effluents from Group 3 were treated with Ag‐AC prior to SIFT‐MS analysis, to assess the removal capacity of Ag‐AC against the reaction products. The synthesis of Ag‐AC was characterized with scanning electron microscopy/energy‐dispersive X‐ray spectroscopy (SEM/EDS). Two‐way analysis of variance (anova ) with post hoc Tukey tests was used for data analysis and determination of a significant difference ( P < 0.05). Results: In Group 1, effluent VOCs and DBPs were detectable at very low levels. In Group 2, the collected effluent aliquots released high concentrations of methanol, propanol, ammonia, chloroform and formaldehyde, which were significantly greater compared to Group 1 ( P < 0.001). SEM/EDS analysis confirmed impregnation of Ag within the AC matrix. The treatment of effluent aliquots with Ag‐AC (Group 3) resulted in a significant reduction in concentrations of acetone, acetic acid, propanol, acetaldehyde, acetonitrile and chloroform, compared to Group 2 ( P < 0.001). The concentration levels of ethanol, methanol, ammonia and formaldehyde remained unaffected ( P > 0.05). Conclusions: In this laboratory setting using extracted human teeth, the chemomechanical preparation of artificially infected root canals resulted in the formation of toxic VOCs and DBPs as effluent suspensions. Their release during aspiration with dental suction indicates that potential environmental hazards should be investigated. The use of silver‐impregnated activated carbon had potential for the point‐of‐use treatment of post‐irrigation effluent aliquots.